Expanded Newborn Screening for Inborn Errors of Metabolism and Genetic Characteristics in a Chinese Population - Guo, Kejian; Zhou, Xuan; Chen, Xigui; Wu, Yili; Liu, Chuanxin; Kong, Qingsheng (Frontiers in Genetics, 2018)
The incidence of inborn errors of metabolism (IEMs) varies dramatically in different countries and regions. Expanded newborn screening for IEMs by tandem mass spectrometry (MS/MS) is an efficient approach for early diagnosis and presymptomatic treatment to prevent severe permanent sequelae and death. To determine the characteristics of inborn errors of metabolism (IEMs) and IEMs-associated mutations in newborns in Jining area, China, 48297 healthy neonates were recruited for expanded newborn screening by MS/MS. The incidence of IEMs was 1/1178 in Jining, while methylmalonic acidemia, phenylketonuria and primary carnitine deficiency ranked the top 3 of all detected IEMs. 30 mutations in 9 IEMs-associated genes were identified in the 28 confirmed cases. As 19 cases with the mutations in PAH, SLC22A5 and MMACHC genes, respectively, it suggested that mutations in the PAH, SLC22A5 and MMACHC genes are the predominant causes of IEMs, leading to the high incidence of phenylketonuria, primary carnitine deficiency and methylmalonic acidemia, respectively. Our work indicated that the overall incidence of IEMs is high and the mutations in PAH, SLC22A5 and MMACHC genes are the leading causes of IEMs in Jining area. Therefore, it is critical to increase the coverage of expanded newborn screening by MS/MS and prenatal genetic consulting in Jining area.